The effect of metformin usage on survival outcomes for hepatocellular carcinoma patients with type 2 diabetes mellitus after curative therapy - Yuan, Bo; Ma, Jichun; Wang, Jing; Hao, Jinyong (Frontiers in Endocrinology, 2022)
Metformin has attracted more attention from researchers for its newly discovered anti-tumor effects. A meta-analysis was performed to reveal the efficacy of metformin on overall survival and recurrence-free survival for HCC patients with T2DM after curative treatment. Databases including PubMed, the Cochrane Library, Web of Science, CNKI, Wangfang and Weipu Database up until May 31, 2022 were searched for relevant studies. STATA 13.0 was used to perform the meta-analysis. A total of 6 studies involving 5936 patients were included in our study. The results from the current study revealed that metformin usage can significantly prolong the 3-year (OR=1.50, 95%CI: 1.22~1.83, P=0.000) and 5-year(OR=1.88, 95%CI: 1.47~2.41, P=0.000) OS and decrease the 1-year(OR=1.31, 95%CI: 1.08~1.59, P=0.007), 3-year(OR=1.88, 95%CI: 1.48~2.37, P=0.000), and 5-year(OR=1.83, 95%CI: 1.40~2.40, P=0.000) recurrence rates. Metformin treatment significantly prolongs the overall survival and decreases the recurrence rate for HCC patients with T2DM after curative HCC therapy.